The impact of the nocebo effect on discontinuation of statin therapy due to myopathy in patients with cardiovascular disease - a review - Jakub Stanek; Patrycja Sornek; Wiktoria Izdebska; Agata Borkowska; Radosław Ciesielski; Anna Kaźmierczak; Anna Kiełb; Anna Mich; Klaudia Perkowska; Igor Pawlak (Nicolaus Copernicus University in Toruń, 2024)
Introduction and purpose of review: Statins are widely used drugs in the prevention of cardiovascular diseases, yet many patients experience side effects of statin use, mainly muscle symptoms, such as myopathy, which often lead to discontinuation of treatment. The aim of this literature review is to assess the role of the nocebo effect in reported muscle symptoms and its impact on statin discontinuation in patients with cardiovascular diseases. Methods: The review analysed the results of several studies, including key publications such as the N-of-1 trial by Wood et al.[1] and the work of Collins et al.[2] on the safety and efficacy of statin therapy. The review covered articles published between 2000 and 2023 that examined the impact of the nocebo effect on statin discontinuation[3-10]. Results: The collected data indicate that the nocebo effect plays a significant role in the reported muscle symptoms during statin use. The study by Wood et al.[1] showed no significant differences in reported symptoms between the groups taking statins, placebo, or receiving no treatment, suggesting that a substantial portion of the symptoms results from the nocebo effect. Similar findings were obtained in the study conducted by the StatinWISE group[4], where patients taking statins and placebo reported a comparable frequency of muscle symptoms. An analysis conducted by Collins et al.[2] indicates that the actual incidence of myopathy associated with statin therapy is much lower than commonly reported. Conclusions: The nocebo effect significantly influences the perceived adverse effects of statins, which may lead to the unjustified discontinuation of these drugs by patients with cardiovascular diseases. Further research is needed to better understand the psychological mechanisms affecting statin tolerance and to develop educational and clinical strategies aimed at minimizing the nocebo effect and improving long-term adherence to therapy.